Neurological disorder in celiac patient after third molars extraction: is there a relation? - Wastner, Bruna da Fonseca; Melzer, Rafaela Savio; Parise, Guilherme Klein; Dobrowolski, Samuel; Stramandinoli-Zanicotti, Roberta Targa; Schussel, Juliana Lucena; Sassi, Laurindo Moacir (ARCHIVES OF HEALTH INVESTIGATION, 2020)
Celiac disease is an immune-mediated gluten-dependent systemic disorder characterized by a specific profile associated with small intestinal lesion. Some of the classical symptoms observed in patients with this condition are nutrient malabsorption, diarrhea, abdominal pain, fatigue and, more recently, neurological symptoms were associated with the disease. Therefore, the objective is to inform an unusual case of a patient with celiac disease that developed severe permanent paresthesia in the superior and inferior gingiva, tongue and palate after tooth extraction e to discuss the relation between both things. Descriptors: Nervous System Disease; Celiac Disease; Molar, Third. References Fasano A, Catassi C. Clinical practice. Celiac disease. N Engl J Med 2012; 367(25):2419-26. Guandalini S, Assiri A. Celiac disease: a review. JAMA Pediatr. 2014;168(3):272-78. de Carvalho FK, de Queiroz AM, Bezerra da Silva RA, Sawamura R, Bachmann L, Bezerra da Silva LA et al. Oral aspects in celiac disease children: clinical and dental enamel chemical evaluation. Oral Surg Oral Med Oral Pathol Oral Radiol. 2015,119(6):636-43. Sanders DS, Patel D, Stephenson TJ, Ward AM, McCloskey EV, Hadjivassiliou M et al. A primary care cross-sectional study of undiagnosed adult celiac disease. Eur J Gastroenterol Hepatol 2003;15(4):407-13. Briani C, Zara G, Alaedini A, Grassivaro F, Ruggero S, Toffanin E et al. Neurological complications of coeliac disease and autoimmune mechanisms: a prospective study. J Neuroimmunol 2008;195(1-2):171-75. Bataineh AB. Sensory nerve impairment following mandibular third molar surgery. J Oral Maxillofac Surg. 2001;59(9):1012-17. Green PH. The many faces of celiac disease: clinical presentation on celiac disease in the adult population. Gastroenterology. 2005;128(4Suppl1): S74-8. Muller AF, Donnelly MT, Smith CM, et al. Neurological complications of celiac disease: a rare but continuing problem. Am J Gastroenterol. 1996; 91(7):1430-35. Chin RL, Snader HW, Brannagan TH, Green PH, Hays AP, Alaedini A et al. Celiac neuropathy. Neurology. 2003;60(10):1581-85. Alaedini A, Green PH, Sander HW, Hays AP, Gamboa AT, Fasano A et al. Ganglioside reactive antibodies in the neuropathy associated with celiac disease. J Neuroimmunol. 2002; 127(1-2):145-48. Oh SJ, Melo AC, Lee DK, Cichy SW, Kim DS, Demerci M et al. Large fiber neuropathy in distal sensory neuropathy with normal routine nerve conduction. Neurology.2001;56(11):1570-72.